Regional Science Matters Studies Dedicated to Walter Isard - Nijkamp, Peter; Rose, Adam.; Kourtit, Karima; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume is a collection of fresh and novel contributions to regional science. They commemorate the scientific inheritance of the founding father of regional science, the late Walter Isard. All papers are written by well-known scholars in the field and serve to highlight the great importance of regional science theory and methodology for a better understanding of current spatial and environmental problems throughout our planet. The book showcases a multidisciplinary panorama of modern regional science research and presents new insights by applying regional science approaches.
Part I: Editorial Introduction -- Part II: Spatial Systems Analysis -- Part III: Regional Growth and Distribution -- Part IV: Regional Policy and Uncertainty -- Part V: Urban Agglomerations.
Keywords: Economics; Geography; Regional planning; Regional economics; Environmental economics; Human Geography; Economics/Management Science; Regional/Spatial Science; Economic Geography; Landscape/Regional and Urban Planning; Environmental Economics; Human Geography